Second order asymptotical efficiency for a poisson process - Gasparyan, S. B. (Հայաստանի ԳԱԱ)
We consider the problem of non-parametric estimation of the mean function of an inhomogeneous poisson process when its intensity function is periodic.
Keywords: Mathematics; Science